2019
DOI: 10.1093/ibd/izz053
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Combining Fecal Calprotectin Levels and Plasma Cytokine Profiles for Individual Prediction of Postoperative Crohn’s Disease Recurrence

Abstract: Background The aims of this study were to characterize the immune response profile in patients with Crohn’s disease (CD) and early postoperative recurrence (POR), to identify predictive biomarkers, and to develop a noninvasive predictive tool for individual estimation of POR risk. Methods Sixty-one patients who had undergone ileocolonic resection for CD were prospectively included and followed up for 24 months. Fecal calprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 45 publications
1
26
0
1
Order By: Relevance
“…It must be underlined that five studies followed up patients for 18–24 months and provide an accurate interpretation of the long‐term association between FC and POR. Moreover, the quality of the studies is more uniform than in the other sections of this review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be underlined that five studies followed up patients for 18–24 months and provide an accurate interpretation of the long‐term association between FC and POR. Moreover, the quality of the studies is more uniform than in the other sections of this review.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the quality of the studies is more uniform than in the other sections of this review. All but two studies 65,70 had a prospective design (Table S1), and in all cases but one, 61 the definition of POR was based on the Rutgeerts score, rendering conclusions more reliable despite the small sample size of most series (Table 6 [57][58][59][60][61][62][63][64][65][67][68][69][70][71][72][73] ).…”
Section: Fecal Calprotectin In Crohn's Diseasementioning
confidence: 99%
“…Recent studies have confirmed fecal calprotectin is the best biomarker for evaluating disease activity in IBD patients [20,21]. However, it is limited in clinical practice owing to its cost and discommodious sample collecting and processing.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological recurrence was assessed by ileocolonoscopy or MRE within 6–12 months after surgery. Endoscopic activity in the neoterminal ileum was graded according to the Rutgeerts score: i0, no lesions; i1, ≤5 aphthous lesions; i2a, lesions confined to the ileocolonic anastomosis; i2b, >5 aphthous lesions with normal mucosa between lesions; i3, diffuse aphthous ileitis with diffusely inflamed mucosa; and i4, diffuse inflammation with larger ulcers, nodules, and/or narrowing, as previously indicated ( 26 ). Recurrence was defined as a Rutgeerts score ≥ i2b ( 27 ).…”
Section: Methodsmentioning
confidence: 99%